Analisis Kesiapan Penerapan Laporan Keuangan Berdasarkan Interpretasi Standar Akuntansi Keuangan (ISAK) 35 (Studi Kasus Di Yayasan Pendidikan SMP SMA Islam Cendekia El Hakim Banda Aceh) - Daffa Ulhaq; Saparuddin Saparuddin; Aqwa Naser Daulay (Universitas 45 Surabaya, 2023)
This research is to determine the Readiness for Implementing Financial Reports Based on the Interpretation of Financial Accounting Standards (ISAK) 35 at the El Hakim Islamic Scholar High School Middle School Education Foundation Banda Aceh. This research uses qualitative research methods and data collection techniques using interview and documentation techniques. This research uses data collection techniques by means of interviews by interviewing several workers at the El Hakim Islamic Scholar Middle School Banda Aceh. The results of this research. The El Hakim Islamic Scholar Middle School Education Foundation has prepared financial reports every month but the financial reports presented are only limited to information on income and cash expenditures of the El Hakim Islamic Scholar Middle School Middle School Education Foundation. The financial reports presented by the El Hakim Islamic High School Middle School Education Foundation are not in accordance with financial reporting standards in accordance with the Interpretation of Financial Accounting Standards (ISAK) 35. This is proven by the form of financial reports prepared by the El Hakim Islamic High School Middle School Education Foundation only limited to information on cash income and expenditure without any information on comprehensive income reports, financial position reports, cash flow reports, reports on changes in net assets, and notes to financial reports. Meanwhile, the Islamic Scholar El Hakim Middle School Middle School Education Foundation was initially not fully ready to implement financial reports in accordance with the Interpretation of Financial Accounting Standards (ISAK) 35.